2020
DOI: 10.1021/acs.inorgchem.0c00008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Cu(II) and Mixed-Valence Cu(I)Cu(II) Clusters Supported by Pyridylamide Ligands

Abstract: A group of copper complexes supported by polydentate pyridylamide ligands H 2 bpda and H 2 ppda were synthesized and characterized. The two Cu(II) dimers [Cu II 2 (Hbpda) 2 (ClO 4 ) 2 ] (1) and [Cu II 2 (ppda) 2 (DMF) 2 ] (2) were constructed by using neutral ligands to react with Cu(II) salts. Although the dimers showed similar structural features, the second-sphere interactions affect the structures differently. With the application of Et 3 N, the tetranuclear cluster (HNEt 3 )-[Cu II 4 (bpda) 2 (μ 3 -OH) 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 68 publications
(103 reference statements)
4
25
0
Order By: Relevance
“…Two reversible waves were observed at the E range of 0.3–0.6 mV vs Ag/AgCl, which could be ascribed to the one-electron oxidation of Cu +1 to Cu +2 and chlorine oxidation, respectively . Recently, Schneider et al reported a mixed-valence pyridylamide-based complex, and the oxidation of Cu +2 and Cu +1 centers was irreversible . In our case, both reversible oxidation and reduction are observed.…”
Section: Resultssupporting
confidence: 58%
“…Two reversible waves were observed at the E range of 0.3–0.6 mV vs Ag/AgCl, which could be ascribed to the one-electron oxidation of Cu +1 to Cu +2 and chlorine oxidation, respectively . Recently, Schneider et al reported a mixed-valence pyridylamide-based complex, and the oxidation of Cu +2 and Cu +1 centers was irreversible . In our case, both reversible oxidation and reduction are observed.…”
Section: Resultssupporting
confidence: 58%
“…The Cu 2p XPS spectra for RT-Cu0.75 ( Fig. 4b) display two peaks appearing at binding energies of 932 eV and 951.8 eV corresponding to Cu 2p3/2 and Cu 2p1/2 respectively; these binding energies are commonly attributed to the presence of Cu 1+ [42]. The signatory satellite peak for Cu 2+ , which appears in the region of 940-945 eV, is not observed in the XPS spectra [43], a result J o u r n a l P r e -p r o o f in accordance with prior studies wherein this oxidation state is often undetected in XPS analysis despite the presence of Cu 2+ [26,44].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…6,7 Generally, a polynuclear complex is held into macromolecules by non-covalent interactions such as hydrogen bonding, hydrophobic, p-p, and electrostatic interactions. [8][9][10] In addition, some Cu(II) multinuclear complexes contain an open coordination site to interact with Lewis basic molecules. 11,12 Interactions between the unsaturated Cu(II) unit and guest molecules usually affect the alteration in the coordination environment of Cu(II) core as well as the molecular packing, leading to chromotropic phenomena.…”
Section: Introductionmentioning
confidence: 99%